1989
DOI: 10.1111/j.1528-1157.1989.tb05476.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Discontinuation of Antiepileptic Drug Therapy in Children with Epilepsy

Abstract: We studied recurrence risks and predictive factors of relapse after antiepileptic drug (AED) discontinuation in a prospective analysis of 425 children with epilepsy who had not had a seizure for at least 2 years (follow-up after withdrawal 1.6-12 years, mean 8 years). Factors closely related by multivariate analysis to relapse were neurologic abnormalities, mental retardation, seizure type (infantile spasms, absence seizures), and appearance or persistence of EEG abnormalities during the course of the illness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
1
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 29 publications
11
61
1
6
Order By: Relevance
“…Furthermore, it can be confirmed [10,12,14,19,20,25] that the vast majority of relapses occur within the 1st year after discontinuation (84% of our cases) and almost all within the 2nd year (93.3%); in this present series, only 3 patients relapsed after the 2nd year.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Furthermore, it can be confirmed [10,12,14,19,20,25] that the vast majority of relapses occur within the 1st year after discontinuation (84% of our cases) and almost all within the 2nd year (93.3%); in this present series, only 3 patients relapsed after the 2nd year.…”
Section: Discussionsupporting
confidence: 49%
“…This time limit of 2 years is considered sufficient by some [10,14,[19][20][21] and not enough by others [11][12][13]15]. The percentage of recovery in our cases (77.5%), which in itself is already very high, would be higher still, if, in the present series, we had included (as in fact many other authors have done) partial benign epilepsies whose natu ral course is favorable and which we normally treat only in particular cases; for this reason we have excluded them from this study which specifically considers AED discon tinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all the studies performed in the last few decades (4,5,8,(17)(18)(19)27) have used a seizure-free period of at least 2 years as the cutoff point for discontinuation of treatment. Studies that analyzed outcome in relation to different seizure-free periods before treatment discontinuation have shown that the seizure-free period correlated positively to favorable outcome (9,25).…”
Section: Applying Our Data To Earlier Modelsmentioning
confidence: 99%
“…Many studies have focused on these issues, and different risk factors for poor prognosis have been recognized (1)(2)(3)(4)(5)(6). Several studies have shown that children with neurological abnormalities or severe forms of epilepsy, such as infantile spasms (IS) or Lennox-Gastaut syndrome (LGS) have poor prognoses in terms of seizure control (3)(4)(5)(6)(7). Other risk factors related to outcome, such as seizure type, age at seizure onset, and EEG abnormalities, have been identified, but the results of earlier studies are not unanimous (1,(6)(7)(8)(9).…”
mentioning
confidence: 99%